Rhabdomyosarcoma of the left atrium of the heart in a child – case report - Stępień, Konrad; Czogała, Małgorzata; Garus, Katarzyna; Wyrobek, Łukasz; Wójcik, Elżbieta; Skalski, Janusz; Balwierz, Walentyna (Pediatria Polska - Polish Journal of Paediatrics, 2018)
Primary tumours of the heart are rare in children. Most of them are benign. Sarcomas predominate among malignant tumours and are characterised by disadvantageous prognosis, especially in the presence of metastases. We present a case of a 16-year-old boy admitted to the hospital with signs of worsening exercise tolerance and suspected left atrial myxoma. The patient was urgently treated with cardiac surgery. Only partial tumour resection was possible. Rhabdomyosarcoma (RMS) embryonale was diagnosed. Stage IV of the disease was established (metastases to the left lung). A good initial response to chemotherapy was observed. In control studies, during the maintenance chemotherapy (15 months from the diagnosis of RMS) progression of the disease (PD) was found: right forearm tumour with metastasis near the left adrenal gland. Despite the intensification of treatment, there was resistance to successive lines of chemotherapy. The patient died of the disease progression.